Beyond Overload: Assessing Cognitive Load to Facilitate Learning Transfer in Virtual Environments - Usman A. ABDURRAHMAN; Abubakar A. ROGO; Abdulkadir A. BICHI; Akibu M. ABDULLAHI (FUDMA Journal of Engineering and Technology, 2025)
Learning transfer, the ability to apply knowledge to new situations, is a foundation of effective education. It involves applying what one has learned in a previous situation to solve problems or navigate new environments. However, this process can fail when a new challenge overwhelms our cognitive resources. Because working memory has a limited capacity, extraneous mental demands can cause overload, hampering performance. This study investigates this phenomenon by measuring the cognitive load of undergraduate students during an immersive virtual reality (VR) driving simulation. We used real-time physiological indicators, pupil diameter and heart rate, to assess the students’ mental workload as they performed complex driving tasks. Our analysis, which categorized different levels of cognitive load, revealed that these psychophysiological measures were directly sensitive to changes in mental demand. The results confirm that tracking physiological signals like heart rate and pupil size provides a valuable window into cognitive load, highlighting its critical role in understanding and facilitating learning transfer within realistic, simulated environments.